Machining of carbon fibre reinforced polymer composites: a preliminary investigation of high power fibre laser - Ahmad Sobri, Sharizal; Heinemann, Robert; Whitehead, David; Afizi Shuaib, Norshah; Abdul Hamid, Mohd Faisal; Mohamed, Mazlan; Wan Ismail, Wan Omar Ali Saifuddin; Teo, Pao Ter; Masri, Mohamad Najmi; Abu Bakar, Mohamad Bashree; Abd Rahim, Erween; Wan Saidin, Wan Ahmad Najmuddin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Carbon fibre reinforced polymer composites (CFRP) is one of the common materials used in machining by various manufacturing industries. The most persistent challenges during the machining, both concerning the consistency of machined surfaces and the properties of the material, are the difficulties such as fibre pull-out, delamination, and decomposition of the material matrix. This preliminary research highlights the laser machining of thick CFRP using a fibre laser of more than 1 kW. Laser machining experiments have been conducted to examine the ability of the fibre laser machine to cut thick CFRP through their high-quality laser beams. Based on the results, the study showed how the heat affected zone can be reduced when the higher cooling period is used. The effects of modulated beam mode include substantial reductions in HAZ compared with other experimental results. In all experimental attempts, substantial damage has occurred. The results are important in assessing the relationship between laser machining parameters and cutting results.